Nurses' Lived Experience of Green Human Resource Management: A Qualitative Study - Shadi Seyedein; Maryam Mesbahi (Kerman University of Medical Sciences, 2020)
Introduction: Experts have considered environmental issues in health departments very important and essential. Understanding nurses' experience of integrated human resource management and environmental management is an important aspect in this regard. Since nurses are a major source of organizational knowledge in hospitals, their point of views can be important and effective. Methods: This study was a qualitative content analysis with 21 nursing staff in hospitals affiliated to Kerman University of Medical Sciences. The participants were selected via purposive sampling method and data were collected through in-depth semi-structured interviews. The data collection continued until data saturation point. The Graneheim and Lundman method was applied to analyze the data. Results: In data analysis, six main and relevant themes were found, including "Green Culture Management", "Green Education", "Green Performance Management", "Green Empowerment", "Green Structure", and "Green Screening". Conclusion: Green human resource management activities are a set of cultural, organizational and individual factors, which strengthen the environmental attitude and performance in hospitals.